Synergistic Antibacterial Activity of Cassia auriculata L. Flowers and Ofloxacin - Devi, Varadharajan Subhadra; Ushanandhini, Dr; AsokKumar, Kuppusamy; UmaMaheswari, Muthuswamy; Sivashanmugham, Andichettiar Thirumalaisamy; Jagannath, Puliyath (Bangladesh Journal of Microbiology, 2012)
A cost effective antimicrobial agent for multi drug resistant organisms, based on the synergistic activity of ofloxacin with ethanolic extract of flowers of Cassia auriculata was determined. The Minimum Inhibition Concentration (MIC) of ethanolic extract using 3 different Gram-positive bacteria, such as Staphylococcus aureus NCIM 2127 and Bacillus subtilis NCIM 2010, and Gram-negative bacteria Escherichia coli NCIM 2118 was found to be around 1024 to 2048 mg/ml. The synergistic activity varied using checkerboard synergy technique. The results of the conducted experiments showed in vitro interactions between antimicrobial agents and plant extract were additive against the strains tested, it also showed synergistic effects between combination of antibiotics and plant extracts with significant reduction in the MICs of the test antibiotics against these strains. It showed maximum synergistic activity against Gram-negative species. The higher synergistic rate was attained against E. coli NCIM 2118, and lowest synergistic shows against S. aureus NCIM 2127. DOI: http://dx.doi.org/10.3329/bjm.v28i2.11824 Bangladesh J Microbiol, Volume 28, Number 2, December 2011, pp 92-94